Curatopia museums and the future of curatorship - Schorch, Philipp 1978-; McCarthy, Conal 1961- (Manchester University Press, 2019)
What is the future of curatorship? Is there a vision for an ideal model, a curatopia, whether in the form of a utopia or dystopia? Or is there a plurality of approaches, amounting to a curatorial heterotopia? This pioneering volume addresses these questions by considering the current state of curatorship. It reviews the different models and approaches operating in museums, galleries and cultural organisations around the world and discusses emerging concerns, challenges and opportunities. The collection explores the ways in which the mutual, asymmetrical relations underpinning global, scientific entanglements of the past can be transformed into more reciprocal, symmetrical forms of cross-cultural curatorship in the present, arguing that this is the most effective way for curatorial practice to remain meaningful. International in scope, the volume covers three regions: Europe, North America and the Pacific.